INTEGRATIVE CELL FORMATION IN CELLULAR MANUFACTURING SYSTEMS - Amasidha K.Athani; Prof. Anyapanyawar R.R; Prof. Patil R.M.; Prof. Vishal A. Bagale (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paper a new integrative view of manufacturing cell formation and both inter-celland intra-cell layout problems arediscussed. Cells formation aredetermined simultaneously through aDynamic Programming algorithm with the objective ofminimizing the inter-cell flow cost. This Dynamic Programmingalgorithm is implemented in a Simulated Annealing approach with Genetic operators to reachnear optimal solutions. Moreover, within this approachby using an Ant Colonyoptimization technique, Theyalso solve the intra-cell layout problem, i.e., theyalso determine howto layout machines within relative cells.(1) An integrated objective function to minimize overall inter-celland intra-cell flow costs instead of merely minimizing the number of inter-cellmovements/costs. (2) The integrative and simultaneous determination of cell formation andtheir layout instead of using sequential approaches. (3) All three phases of cell formation, intercelland intra-cell layout design problems, which are all important for overall performance ofthe system, and (4) An easy to code and solve integrated procedure through implementingmetaheuristic approaches.